A Moment of Letting Go: Iris Murdoch and the Morally Transformative Process of Unselfing. Issue 1 (2nd February 2018) - OLSSON, ANNA‐LOVA
Abstract: Higher education as a personal, intellectual and moral cultivation is a longstanding ideal that is constantly challenged by the view that education is merely the development of specific skills for vocational and personal success. Much research argues that the latter understanding makes education a technical affair that creates an egocentric emphasis on the individual students' ambitions and desires. This article joins in the defence of the former ideal by enquiring into the moral dimensions of education. This is done by turning to Iris Murdoch's idea of moral transformation, with a specific focus on the idea of unselfing . The main argument is that unselfing is a transformative process characterised by a growing attunement to the surrounding world, and the interconnectedness of goal and process is emphasised. Also, to gain a deeper understanding of what unselfing entails I turn to the idea of attention. It is understood as having a specific direction, outward from the egocentric, and as enabling unselfing . The article concludes by suggesting that unselfing can offer a challenge to (higher) education as it entails a moment of letting go of plans and narratives, and of surrendering to the influence of an existence that exceeds the individual. This moment is of relevance to education as it is crucial to the possibility of growing as a moral being as it cultivates a moral manner of relating to others.